Strengthening Workers' Participation in Corporate Governance - Binghay, Virgel C. (Philippine Journal of Labor and Industrial Relations, 2021)
This paper concerns itself with the relationship of two management strategies perceived to lead companies towards a better position in today's era: workers' participation and corporate governance. This paper suggests that the inception of workers' participation in corporate governance is a vital factor for an industry to survive in this competitive world as it helps ensure industrial peace, quality goods and services, and company productivity. Corporations are therefore encouraged to rethink of the promises of securing workers' involvement in all facets of business processes. Governments too are encouraged to provide for platforms that will institutionalize workers' involvement in companies' decision-making.